2004
DOI: 10.1093/hmg/ddh157
|View full text |Cite
|
Sign up to set email alerts
|

The unique transcriptome through day 3 of human preimplantation development

Abstract: Successful human development is dependent upon a cascade of events following fertilization. Unfortunately, knowledge of these critical events in humans is remarkably incomplete. Although hundreds of thousands of human embryos are cultured yearly at infertility centers worldwide, the vast majority fail to develop in culture or following transfer to the uterus. In this study, we sought to characterize global patterns of gene expression in individual, normal embryos during the first three days of embryonic life u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(203 citation statements)
references
References 48 publications
11
189
1
Order By: Relevance
“…the 8-cell stage and another increase to the blastocyst stage (Zhang et al 2012). These authors suggest the changes observed for both H3K4me3 and H3K27me3 from the 4-cell to 8-cell stage may be associated with embryonic genome activation, (Zhang et al 2012) which occurs during this time in human embryos (Dobson et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…the 8-cell stage and another increase to the blastocyst stage (Zhang et al 2012). These authors suggest the changes observed for both H3K4me3 and H3K27me3 from the 4-cell to 8-cell stage may be associated with embryonic genome activation, (Zhang et al 2012) which occurs during this time in human embryos (Dobson et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Although in these studies, in patients with good prognosis, fewer embryos were transferred, in our survey, between the two groups, the number of embryos transferred remained unchanged. Many studies also compared day 2 with day 3 ETs, but there seems to be no consensus (4,5,21,22). For example, Laverge et al (6) observed similar clinical pregnancy and implantation rates between days 2 and 3, while overall embryo quality scores were lower on day 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study it was suggested that the embryo selection occurs during the cleavage period. Therefore, a delay in ET to day 3 may lead to selection of better quality embryos for transfer (22). In a retrospective study, Dawson et al (7) showed that the pregnancy rate was higher with day 3 ET, but this was not statistically significant (35% vs. 31%, NS); however, implantation rates showed a significant difference (23% vs. 19%, P < 0.05) and the miscarriage rate was lower on day 3(6% vs. 2%, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In human, the embryonic gene becomes active at 4-8 cell stage which is maintained throughout adult life. Dobson et al, [70] reported several studies that documented key events that follow fertilization in humans, such as a decrease in abundance of individual mRNAs, activation of bulk mRNA transcription following a quiescent period and nascent expression of a few individual known genes that were previously characterized in other organisms. They also validated reports that demonstrate robust patterns of stage specific gene expression, representing maternal genes that are deactivated (down-regulated) and zygotic genes that are activated (upregulated) using their microarray studies.…”
Section: Transcriptomicsmentioning
confidence: 99%